Targeting Immunologic Pathways in Eosinophilic Granulomatosis With Polyangiitis: Translating Emerging Evidence Into Clinical Practice. - Wilson-Morkeh,H; Seluk,L; Bosch,P; Aguiar,C; Thiel,J; Hellmich,B; Wechsler,ME; Siddiqui,S (Allergy, 2026)
Eosinophilic granulomatosis with polyangiitis (EGPA) is a rare and potentially life-threatening systemic, inflammatory disease with multi-organ manifestations, variable presentation and complex pathology. Multiple interconnected immunological pathways are implicated in EGPA pathology, including a type-2 immune response driving predominantly eosinophilic inflammation, B-cell mediated autoimmunity, neutrophil activation, and the generation of pathogenic anti-neutrophil cytoplasmic antibodies, all of which can contribute to tissue/organ damage. High-dose glucocorticoids are the mainstay treatment for EGPA, but over the past two decades the development of biologic treatments targeting interleukin (IL)-5, eosinophils and B-cells has revitalized the treatment landscape. Mepolizumab, a humanized monoclonal antibody that specifically targets IL-5, and benralizumab, which targets the IL-5 receptor (IL-5Rα), are both approved for the treatment of patients with non-severe relapsing or refractory EGPA. In Phase III trials, these biologics have demonstrated favorable safety profiles and efficacy, with treatment leading to remission induction, remission maintenance, and oral glucocorticoid sparing benefits. However, as understanding of the full complexity of EGPA pathogenesis improves, new treatment targets are emerging. Consequently, understanding key pathogenic mechanisms at the patient level, enabling a more tailored treatment approach, is an important goal for future research.